Public Health Impact of Legal Termination of Pregnancy in the US: 40 Years Later - John M. Thorp (Scientifica)
During the 40 years since the US Supreme Court decision in Doe versus Wade and Doe versus Bolton, restrictions on termination of pregnancy (TOP) were overturned nationwide. The use of TOP was much wider than predicted and a substantial fraction of reproductive age women in the U.S. have had one or more TOPs and that widespread uptake makes the downstream impact of any possible harms have broad public health implications. While short-term harms do not appear to be excessive, from a public perspective longer term harm is conceiving, and clearly more study of particular relevance concerns the associations of TOP with subsequent preterm birth and mental health problems. Clearly more research is needed to quantify the magnitude of risk and accurately inform women with the crisis of unintended pregnancy considering TOP. The current US data-gathering mechanisms are inadequate for this important task.